INFLUENCE OF TAXES, EXCHANGE RATE, PROFITABILITY, AND TUNNELING INCENTIVE ON COMPANY DECISIONS OF TRANSFERRING PRICING - Citra Syifa Azzura; Aditya Pratama (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2019)
This study aims to analyze the influence of Taxes, Exchange Rate, Profitability, and Tunneling Incentive on Company Decisions to Make Transfer Pricing in manufacturing companies. The dependent variable in the study is transfer pricing while the independent variables in this study are tax, exchange rate , profitability, and tunneling incentive .The sample was chosen using a purposive sampling method with certain criteria. In accordance with the required data, namely secondary data, this data collection method uses documentation techniques based on the 2013-2017 financial statements. So that a sample of 17 manufacturing companies can be obtained.The results of the analysis of this study indicate that taxes affect the transfer pricing decision. Exchange rates and profitability have no effect on transfer pricing decisions. While the tunneling incentive affects the transfer pricing decision .